Determinants of governmental redistribution - Klaus Gründler; Sebastian Köllner (Julius Maximilian University of Würzburg, Chair of Economic Order and Social Policy, 2015)
This paper investigates the major drivers of governmental redistribution. We retest the Meltzer-Richard hypothesis and account for a plethora of political, institutional, and cultural forces that influence the scope of redistribution. Extended and harmonized data on effective redistribution recently provided by the SWIID allows for the assessment of the origins of governmental redistribution for a broad sample of countries. Our results confirm the Meltzer-Richard hypothesis, indicating that the link between market inequality and redistribution is even stronger when using perceived inequality measures. We support the decisive role of the median voter, though also approving a crucial role of top incomes. Political and institutional conditions as well as cultural aspects significantly influence governments in their decisions regarding the amount of redistribution.
Keywords: C23; D31; D72; H11; 330; Redistribution; Inequality; Economic Policy; Dynamic Panel Data